Remote laboratory prototype for automation of industrial processes and communications tests (2014)
This paper presents the initial phase of the approach and implementation of a prototype of virtual infrastructure for teaching and lab development in the areas of Industrial Automation and Industrial Communications. The proposed prototype allows remote lab practice using: internet, VMware virtualization and management through Netlab. It allows easy and permanent access to the automation software and hardware necessary for an adequate student experience with real devices.